Inflammation Biomarkers and Correlation to Wound Status After Full-Thickness Skin Grafting - Saleh, Karim; Strömdahl, Ann-Charlotte; Riesbeck, Kristian; Schmidtchen, Artur (Frontiers in Medicine, 2019)
Background: A surgical site infection (SSI) is believed to be the result of an exaggerated inflammatory response. Objective: Examine the relationship between clinical status and inflammation biomarkers in full-thickness skin grafting wounds. Methods: Twenty patients planned for facial full-thickness skin grafting were enrolled. A week after surgery, all graft wounds were clinically assessed using a 3-step scale for inflammation (low, moderate, high). All wounds were swabbed for routine microbiological analysis and assessment of numbers of aerobic bacteria. Tie-over dressings from all patients were collected and used for wound fluid extraction and subsequent analysis of MMPs, cytokines, and NF-κB inducing activity. Results: Wounds with a high degree of inflammation contained increased total MMP activity (P≤ 0.05) in their corresponding fluids. Likewise, the level of the cytokines IL-1ß, IL-8, IL-6, TNF-α was analysed, and particularly IL-1ß was discriminatory for highly inflamed wounds (P≤ 0.01). Moreover, bacterial loads were increased in highly inflamed wounds compared to wounds with a low degree of inflammation (P≤ 0.01). NF-κB activation in the monocytic cell line THP-1 was significantly higher when these cells were stimulated by wound fluids with a high degree of inflammation (P≤ 0.01). Growth of S. aureus in wounds did not vary between wounds with different degrees of inflammation (chi-square 3.8, P = 0.144). Conclusion: Biomarkers analysed from tie-over dressings correlated to clinical wound healing in full-thickness skin grafting.